Timing performance of radiation hard MALTA monolithic pixel sensors. (15th March 2023) - Gustavino, G.; Allport, P.; Asensi, I.; Berlea, D.V.; Bortoletto, D.; Buttar, C.; Dachs, F.; Dao, V.; Denizli, H.; Dobrijevic, D.; Flores, L.; Gabrielli, A.; et al.
Abstract: The MALTA family of Depleted Monolithic Active Pixel Sensor (DMAPS) produced in Tower 180 nm CMOS technology targets radiation hard applications for the HL-LHC and beyond. Several process modifications and front-end improvements have resulted in radiation hardness up to 2 × 10 15 1 MeV neq /cm 2 and time resolution below 2 ns, with uniform charge collection efficiency across the pixel of size 36.4 × 36.4 μm 2 with a 3 μm 2 electrode size. The MALTA2 demonstrator produced in 2021 on high-resistivity epitaxial silicon and on Czochralski substrates implements a new cascoded front-end that reduces the RTS noise and has a higher gain. This contribution shows results from MALTA2 on timing resolution at the nanosecond level from the CERN SPS test-beam campaign of 2021.